2022
DOI: 10.1002/iid3.748
|View full text |Cite
|
Sign up to set email alerts
|

Two formulations of coronavirus disease‐19 recombinant subunit vaccine candidate made up of S1 fragment protein P1, S2 fragment protein P2, and nucleocapsid protein elicit strong immunogenicity in mice

Abstract: Introduction: Coronavirus disease (COVID-19) is ongoing as a global epidemic and there is still a need to develop much safer and more effective new vaccines that can also be easily adapted to important variants of the pathogen. In the present study in this direction, we developed a new COVID-19 vaccine, composed of two critical antigenic fragments of the S1 and S2 region of severe acute respiratory syndrome coronavirus 2 as well as the whole nucleocapsid protein (N), which was formulated with either alum or al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…A combined vaccine consisting of two immunogenic spike protein regions and a full-length N antigen formulated with aluminum hydroxide with or without monophosphoryl lipid A was studied by Özcengiz et al The authors demonstrated recognition of the recombinant proteins by the sera of COVID-19 convalescents, as well as induction of high titers of anti-P1, anti-P2 and anti-N IgG (including neutralizing antibodies) and interferon-gamma (IFN-γ) secreting T cells in mice. The developers note that the vaccine with adjuvant containing monophosphoryl lipid A is more suitable for immunization of elderly individuals, because it promotes the development of Th1 immune response, while the use of aluminum hydroxide alone is more justified for vaccination of young people [ 51 ].…”
Section: Development Of N-based Broadly Protective Vaccine Prototypesmentioning
confidence: 99%
“…A combined vaccine consisting of two immunogenic spike protein regions and a full-length N antigen formulated with aluminum hydroxide with or without monophosphoryl lipid A was studied by Özcengiz et al The authors demonstrated recognition of the recombinant proteins by the sera of COVID-19 convalescents, as well as induction of high titers of anti-P1, anti-P2 and anti-N IgG (including neutralizing antibodies) and interferon-gamma (IFN-γ) secreting T cells in mice. The developers note that the vaccine with adjuvant containing monophosphoryl lipid A is more suitable for immunization of elderly individuals, because it promotes the development of Th1 immune response, while the use of aluminum hydroxide alone is more justified for vaccination of young people [ 51 ].…”
Section: Development Of N-based Broadly Protective Vaccine Prototypesmentioning
confidence: 99%
“…Priming of cross-reactive nucleoprotein-specific T cells alone was 60% protective [164]. Similarly, other teams also designed and developed multiple recombinant vaccines based on nucleoproteins [165][166][167][168].The results showed that recombinant vaccines could significantly increase the levels of serum neutralizing antibody and total immunoglobulin [165], and induce strong specific lymphocyte proliferative response and T cell response [165]. The antigen specificity level of interferon-γ in splenocytes of immunized mice increased [166,167].…”
Section: Vaccine Research and Developmentmentioning
confidence: 98%
“…Similarly, other teams also designed and developed multiple recombinant vaccines based on nucleoproteins [165][166][167][168].The results showed that recombinant vaccines could significantly increase the levels of serum neutralizing antibody and total immunoglobulin [165], and induce strong specific lymphocyte proliferative response and T cell response [165]. The antigen specificity level of interferon-γ in splenocytes of immunized mice increased [166,167]. The recently published reviews provided a good summary of the role of SARS-CoV-2 nucleocapsid protein in antiviral immunity and vaccine development [169,170].…”
Section: Vaccine Research and Developmentmentioning
confidence: 99%
“…Proteins Induces Immune Response. An intriguing approach, combining the N protein with subunit S1 or S2 of the spike protein utilizing BALB/c mice demonstrated a higher induction of specific S1, S2, and N IgG antibodies and neutralizing activity and IFN-γ production in all immunized animals [80].…”
Section: Combination Of Nucleocapsid and Spike Recombinantmentioning
confidence: 99%
“…An intriguing approach, combining the N protein with subunit S1 or S2 of the spike protein utilizing BALB/c mice demonstrated a higher induction of specific S1, S2, and N IgG antibodies and neutralizing activity and IFN- γ production in all immunized animals [ 80 ]. Hong et al [ 81 ] investigated the combination of the N protein with the S protein using an E. coli expression system, wherein they fused the RBD of the spike protein with the tetanus toxoid epitope P2 and the whole N protein.…”
Section: The Potential Use Of Nucleocapsid As Vaccine Antigenmentioning
confidence: 99%